EFFECT OF RADIATION AND INJECTION ON A NEWTONIAN FLUID FLOW DUE TO POROUS SHRINKING SHEET WITH BRINKMAN MODEL - Maranna, Thippaiah; Mahabaleshwar, Ulavathi Shettar; Bognar, Gabriella Vadaszne; Öztop, Hakan Fehmi Fehmi (Begell House Inc, 2024)
This paper is centered on an analytical solution of radiation and injection effects on a Newtonian fluid flow due to a porous shrinking sheet with the Brinkman model. For the momentum equations, the Brinkman model is employed. In addition, the effects of radiation and injection factors on temperature and concentration are considered. Consideration is given to the cross-diffusion relationship between temperature and concentration. By using a similarity transformation, the flow and heat transfer-related coupled partial differential equations are transformed into coupled ordinary differential equations that are non-linear. The exact solutions are obtained for the governing equations analytically. Energy, as well as concentration equations, are solved using the Euler-Cauchy equation method. The accuracy of the method is verified with the existing results, and they are found to be in good agreement. The effect of various physical parameters such as the Darcy number, shrinking parameter, radiation, Soret, and Dufour numbers on non-dimensional velocity, temperature, and concentration profiles have been graphically interpreted. It is found that the velocity profile decreases as the porous parameter increases asymptotically. The temperature increases with an increase in the parameter value of the radiation. The shear stress profile improves when the inverse Darcy value is raised, but it degrades when the suction parameter is moved. Heat transfer rate increases with an increasing Soret number for small values of Dufour number, but it slightly decreases with an increasing Soret number for larger values of Dufour number, and the mass transfer rate reacts in the opposite direction.
Keywords: radiation; mass transfer; Brinkmann ratio; Soret and Dufour numbers; Darcy number